THE JOURNAL OF EMOTIONAL STATE: ABSTRACT ART FOR REFLECTION AND THERAPY OF NEGATIVE EMOTIONS - Riyapun, Wasawat (Fine Arts Journal: Srinakharinwirot University, 2024)
“The Journal of Emotional States: Abstract Art for Reflection and Therapy of Negative Emotions” is an article that aims to present works in the field of visual arts. The author draws on his own experiences with negative emotions for receiving the therapy with art strategies (Art Therapy), with the goal to restore both physical and mental symptoms, aiming for inner transformation. Each creation process is different each time, influenced by the emotional state at the time, and it is focused on exploring emotions, thoughts, self-understanding, and self-expression. The works are documented as a journal that relies on the Abstract Art techniques to create textures or special characteristics conveying emotions triggered by stimuli through various materials. The artist records these emotions on surfaces like paper, using different textures and sizes, as a means to capture moments of emotional states in various situations. This process is intended to reflect on mindfulness, emotional control, and self-awareness amid emotional turbulence. The objective is to present a reflection of the emotional state arising from personal experiences such as anger, suffering, and sadness and examines ways to control these emotions through a journaling process that translates into art. Additionally, theoretical, philosophical, and ethical insights are investigated to understand human emotional management. Through visual art techniques aligned with specific emotional experiences, the artist aims to produce therapeutic artworks, focusing on self-exploration of emotions in different situations. This creative process employs abstract art to communicate self-discipline and mindfulness, resulting in a collection of two series of therapeutic art pieces.